Effect of quantum tunneling on the efficiency of excitation energy transfer in plasmonic nanoparticle chain waveguides - Ilawe, Niranjan V. (2018)
We present a detailed analysis of the electronic couplings that mediate excitation energy transfer (EET) in plasmonic nanoantenna systems using large-scale quantum dynamical calculations. To capture the intricate electronic interactions in these large systems, we utilize a real-time, time-dependent, density functional tight binding (RT-TDDFTB) approach to characterize the quantum-mechanical efficiency of EET in plasmonic nanoparticle chains with subnanometer interparticle spacings. In contrast to classical electrodynamics methods, our quantum dynamical calculations do not predict a monotonic increase in EET efficiency with a decrease in interparticle spacing between the nanoparticles of the nanoantenna. Most notably, we show a sudden drop in EET efficiencies as the interparticle distance approaches subnanometer length scales within the nanoparticle chain. We attribute this drop in EET efficiency to the onset of quantum charge tunneling between the nanoparticles of the chain which, in turn, changes the nature of the electronic couplings between them. We further characterize this abrupt change in EET efficiency through visualizations of both the spatial and time-dependent charge distributions within the nanoantenna, which provide an intuitive classification of the various types of electronic excitations in these plasmonic systems. Finally, while the use of classical electrodynamics methods have long been used to characterize complex plasmonic systems, our findings demonstrate that quantum-mechanical effects can result in qualitatively different (and sometimes completely opposite) results that are essential for accurately calculating EET mechanisms and efficiencies in these systems.